Pemanfaatan Platform Noice Sebagai Sarana Mengembangkan Audiobook Cerita Rakyat Madura - Setyawan, Arief; Kusuma, Emy Rizta (Universitas Muhammadiyah Surabaya, 2024)
The focus of this research is the utilization of technological developments combined with local Madurese literature. From this comes the research objective to optimize the features on the noice platform to develop the Audiobook of Madurese Folklore. The results of this research are expected to be an alternative in enjoying books or reading materials in a different way, namely by listening. The research method used in this research is development with the 4D model (Thiagarajan, Dorothy, and Melvyn) which consists of four development stages, namely determination, design, development, and dissemination. The results of this study include: 1) The product is produced in the form of Audiobook of Madurese Folklore which is effective to be utilized in understanding reading sources by listening, 2) The Noice platform is effectively used as a means of developing Audiobooks with reading material for Madura Folklore. 3) Audiobooks of Madurese folklore produced through the Noice platform can be operated on computers (laptops) and android/mobile phones easily and practically as long as they are connected to the internet network.